Clinical evaluation and treatment of chronic bowel symptoms following cancer in the colon and pelvic organs. (4th May 2019) - Larsen, Helene Mathilde; Borre, Mette; Christensen, Peter; Mohr Drewes, Asbjørn; Laurberg, Søren; Krogh, Klaus; Fassov, Janne
Abstract: Background: Chronic gastrointestinal symptoms are common among patients surviving surgery and/or radio-/chemotherapy for cancer in the pelvic organs. However, little is known about the pathophysiology behind symptoms or the effect of treatment. The aim of the present study was to present the results of clinical evaluation and treatment of patients with chronic bowel symptoms after treatment for cancer in the colon or pelvic organs. Material and methods: All patients referred to our department of gastroenterology between May 2016 and June 2018 with chronic bowel symptoms after treatment for cancer in the colon or pelvic organs were prospectively evaluated. Results: In total, 60 patients had been referred. The patients were treated for cancer in the right colon ( n  = 31), sigmoid colon ( n  = 1), rectum ( n  = 14), anal canal ( n  = 4), cervix uteri ( n  = 5), corpus uteri ( n  = 2), ovary ( n  = 2), and prostate ( n  = 1). The median time from cancer treatment to referral was 5.5 (range 1–36) years. Symptoms mainly included frequent bowel movements (65%), loose stools (87%), urgency for defecation (57%), and fecal incontinence (50%). A specific cause of bowel dysfunction was found in 48 (80%) of the patients and 21 (35%) had more than one cause of bowel symptoms. Bile acid malabsorption was present in 35 patients and small intestinal bacterial overgrowth was detected in 32. Treatment included bile acid sequestrants ( n  = 36), antibiotics ( n  = 33), loperamide ( n  = 21), and dietary intervention ( n  = 20). Major improvement in bowel symptoms was reported by 23 (38%) patients, while another 27 (45%) reported some improvement. Conclusion: Most patients with chronic bowel symptoms following cancer in the colon or pelvic organs will benefit from expert clinical evaluation and targeted treatment.